Association of Autologous Costal Cartilage Harvesting Techniques with Donor Site Pain in Patients Undergoing Augmentation Rhinoplast - Mehmood, Mehwish; Aslam, Ayesha; Aman, Sameena; Ali, Ahmed; Feroze, Hira; Saleem, Nousheen; Mumtaz, Hassan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the relationship between postoperative pain and the harvesting of autologous costal cartilage grafts using either a muscle-sparing technique with blunt dissection or a muscle-cutting technique with electrocautery in patients undergoing augmentation rhinoplasty. Study Design: Quasi-experimental study. Place and Duration of Study: Plastic Surgery Department, Fauji Foundation Hospital, Rawalpindi Pakistan, from Oct 2022 to Jun 2023. Methodology: A total of 32 patients, aged 15 to 35 years and of both genders, undergoing elective augmentation rhinoplasty with no medical comorbidities, were divided into two groups. Patients who were undergoing surgery due to acute nasal trauma, nasal patency, nasal polyps, and other pathological causes were excluded. Group-A received augmentation rhinoplasty via the muscle-sparing technique, while Group-B received the surgery via muscle-cutting technique using electrocautery. Patients in both groups were assessed in terms of postoperative donor site pain. Results: The mean age in Group-A was 20.7±5.5 years while in Group-B, it was 21.7±4.9 years. The comparison of mean pain scores at rest (p<0.005) was calculated for both groups on 0 to 10th postoperative day that resulted in significant decrease for Group-A. The mean pain score during movement from the 0 to 10 postoperative days and after 1 month (p=0.003), was also compared between both groups and it was significantly lower in Group-A as compared to Group-B. Conclusion: Muscle-sparing techniques have shown to be superior to muscle-cutting techniques for harvesting autologous costal cartilage grafts, both in terms of resting pain and pain during movement.